Additional intragenic promoter elements of the Xenopus 5S RNA genes upstream from the TFIIIA-binding site. - Keller, H J (1990)
The major promoter element of the Xenopus laevis 5S RNA gene is located within the transcribed region of the gene and forms the binding site for the transcription initiation factor TFIIIA. We report an analysis of deletion and substitution mutations within the coding region of the major oocyte-type 5S gene of X. laevis. Our results differ from those of previous mutagenesis studies conducted on the somatic-type genes of Xenopus borealis and X. laevis. Transcription assays in whole oocyte S-150 extracts, with both oocyte- and somatic-type mutants, revealed additional promoter elements between the start site for transcription and the binding site for TFIIIA. These sequences regulate the efficiency of binding TFIIIC, a transcription factor required by the genes transcribed by RNA polymerase III containing intragenic promoters. Under TFIIIC-limiting conditions, the somatic-type gene had a 10-fold-higher affinity for TFIIIC than did the major oocyte-type 5S gene. One mutation in the oocyte-type gene (nucleotides +33 to +39) reduced TFIIIC affinity and transcriptional activity four- to fivefold. Differences in TFIIIC affinity between oocyte- and somatic-type genes may contribute to the differential transcription of these genes observed during Xenopus embryogenesis.